Postpartum Spinal Osteoporosis: An Unusual Cause of Low Back Pain - Berrin Gündüz,; Belgin Erhan,; Merih Sarıdoğan,; Nurgül Elbaşı,; Huri Özdoğan, (Archives of Rheumatology, 2010)
Postpartum spinal osteoporosis (PPSO) is a rare condition characterized by osteoporosis associated with pregnancy. The most common symptoms are low back pain and loss of height due to vertebral compression fractures. It is observed in the last trimester of pregnancy or subsequent to delivery. Herein; we report 2 cases of PPSO who presented with low back pain in the postpartum period, aiming to draw attention to this unusual cause of low back pain. (Turk J Rheumatol 2010; 25: 47-9)